PEROXIDASE ACTIVITY IN MAIZE INBRED LINES RESISTANT OR SUSCEPTIBLE TO MAIZE DWARF MOSAIC VIRUS - SOUZA, ISABEL REGINA PRAZERES DE; OLIVEIRA, ELIZABETH DE; PERES, MARILDA AUGUSTA; OLIVEIRA, ANTÔNIO CARLOS DE; PURCINO, ANTÔNIO ÁLVARO CORSETTI (International Journal of Maize & Sorghum, 2010)
Peroxidase (EC 1.11.1.7) activity levels were analyzed in maize seedling inbred lines contrasting with their resistance to maize dwarf mosaic virus (MDMV). Groups of noninoculated resistant and susceptible inbred lines showed different levels of guaiacol peroxidase activity at the seedling stage, with 78 % of susceptible inbred lines presenting enzyme activity values below 91.46A470min-1gFW. However, the zymogram patterns of peroxidase did not allow the differentiation of non-inoculated resistant or susceptible inbred lines. The virus complex induced a general enhancement of enzyme activity, without qualitative changes in the isoenzymes, when inoculated into resistant or susceptible inbred lines. However, a quantitative change, with 19% OD average increase in a moderately anionic isoform was observed in some resistant inbred lines in response to virus inoculation. Our results could suggest that peroxidase activity prior to infection, and the increase in activity of an specific anionic isoform in some resistant inbred lines, due to virus inoculation, could be related to a defense mechanism against MDMV.